2019
DOI: 10.1007/s00204-019-02437-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and in vitro models of drug-induced cholestasis

Abstract: Cholestasis underlies one of the major manifestations of drug-induced liver injury. Drug-induced cholestatic liver toxicity is a complex process, as it can be triggered by a variety of factors that induce 2 types of biological responses, namely a deteriorative response, caused by bile acid accumulation, and an adaptive response, aimed at removing the accumulated bile acids. Several key events in both types of responses have been characterized in the past few years. In parallel, many efforts have focused on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 182 publications
(268 reference statements)
0
37
1
Order By: Relevance
“…This complied with the observations of the present study, which showed suppression of BSEP activity by ATA, NEFA, and CsA in HepaRG cell cultures, albeit no altered gene expression of the transporter was observed. Nevertheless, it should be emphasized that besides BSEP inhibition, other molecular initiating events underlie cholestatic liver injury, including effects on alternative transporters, hepatocellular changes, and bile canalicular changes (Gijbels et al 2019). In this regard, NEFA has been reported to inhibit OATP(s) and multidrug resistance protein 1 (MDR1) transporter (Dragovic et al 2016;Kolaríc et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This complied with the observations of the present study, which showed suppression of BSEP activity by ATA, NEFA, and CsA in HepaRG cell cultures, albeit no altered gene expression of the transporter was observed. Nevertheless, it should be emphasized that besides BSEP inhibition, other molecular initiating events underlie cholestatic liver injury, including effects on alternative transporters, hepatocellular changes, and bile canalicular changes (Gijbels et al 2019). In this regard, NEFA has been reported to inhibit OATP(s) and multidrug resistance protein 1 (MDR1) transporter (Dragovic et al 2016;Kolaríc et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a 50 × concentrated BA mix of the five most abundant BAs present in human serum was added to HepaRG cells together with the cholestatic drugs. This setup enabled more close resemblance to the in vivo situation during cholestasis, to detect BA-selective sensitization towards toxic effect of cholestatic drugs, as well as to distinguish cholestatic hepatotoxicity from non-cholestatic hepatotoxicity (Sharanek et al 2017;Gijbels et al 2019). In this study, the cholestatic drugs ATA, CsA, and NEFA were selected based on literature data (Oorts et al 2016;Rakotondravelo et al 2012).…”
Section: Assessment Of Working Concentrations Of Cholestatic Drugs Inmentioning
confidence: 99%
“…These nuclear receptors equally play a key role in cholestasis, in particular by mediating the adverse response and inducing the expression of genes involved in counteracting bile acid accumulation, including those coding for hepatic transporters and biotransformation enzymes. 2,4 Triclosan causes hepatic inflammation 80 , oxidative stress 81 , mitochondrial toxicity 82,83 , cell cycle arrest and apoptosis 81,84 . Triclosan also suppresses microfilament remodeling and cell membrane ruffling 85 , and affects a number of signaling cascades, including protein kinase B 86,87 and extracellular signal-regulated kinases 1/2 87 , all that collectively promote cholestatic liver injury.…”
Section: Triclosanmentioning
confidence: 99%
“…17 In rats, alpha-naphthylisocyanate evokes hepatic inflammation 18 , oxidative stress 14 , endoplasmic reticulum stress 19 and mitochondrial toxicity 20 , all being key events in cholestatic liver injury. 2,4 Alpha-naphthylisocyanate alters the expression and/or activity of a number of hepatic transporters, including the bile salt export pump, multidrug resistance-associated protein 2/3 and multidrug resistance protein 3. [21][22][23] Furthermore, alpha-naphthylisocyanate disrupts hepatic tight junctions 24,25 , decreases membrane fluidity 26 and causes bile canaliculi dilatation 27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation